Development of Interactive Media Using Kodular in The Learning Evaluation Course: Supporting the Implementation of the Merdeka Curriculum - Pipi Deswita; Adelia Alfama Zamista; Sylvina Tebriani (Postgraduate, University of Mataram, 2025)
This study addresses the lack of specific and interactive teaching media aligned with the Merdeka Curriculum in the Learning Evaluation course for Physics Education students. The research aims to develop and validate Kodular-based interactive media that facilitate independent and competence-based learning. The study employed the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, expert validation sheets, and practicality questionnaires, and analyzed using descriptive statistics to determine validity and practicality levels. The validation results showed that the media achieved very high scores in content, language, and media feasibility, indicating strong validity. Implementation trials involving lecturers and students demonstrated high practicality, particularly in ease of use, clarity, and relevance of content. The Kodular-based media integrates quizzes, simulations, and collaborative features that enhance engagement and understanding of evaluation concepts. The findings conclude that the developed interactive media is both valid and practical for supporting the implementation of the Merdeka Curriculum and improving students’ abilities in designing contextual and authentic learning evaluation instruments